Overconfident Behavior in a Security Market, the Implication of Self Deceptive Behavior in Price Discovery Processes â A Market Experiment - Kufepaksi, Mahatma (Journal of Indonesian Economy and Business, 2008)
People may suffer from overconfidence in their daily activities. According toÂ psychological research, less informed individuals may suffer from overconfidence. EmpiricalÂ research shows that investors suffer from transaction losses due to overconfidence. ThisÂ current research is an experimental research project that addresses these issues. According toÂ the research design, all investors are classified into three groups based on their scores ofÂ overconfidence, namely the less informed investors, the rational (average) investors, and themore informed investors. In order to observe the responses of the groups of investors whenÂ they receive valuable information, the research employs four different types of treatmentsÂ consisting of the condition of no market information, the provision of guidance of securityÂ prediction, the good news and the bad news.The research demonstrates that the less informed investors are inclined to assess theÂ precision of their knowledge and information excessively so that they produce a higher meanÂ of prediction and price errors than those of the more informed investors in all experimentalmarket sessions, except in the market session of good news. The phenomenon indicates thatÂ less informed investors conduct a self deceptive behavior. The result of the research alsoÂ shows that although the less informed investors have higher mean of prediction or priceÂ errors, they have a chance to gain profit as long as they are able to deliver the predicted valueÂ of the security accurately which is closer to the market price that reflects the expected price ofthe majority of the market players.Keywords: Overconfidence, self-deception, price (prediction) error; transaction losses